Demand and growth regimes in finance-dominated capitalism and a progressive equality-, sustainability- and domestic demand-led alternative: A post-Keynesian simulation approach - Eckhard Hein; Franz Prante; Alessandro Bramucci (PSL Quarterly Review, 2023)
Making use of a post-Keynesian/Kaleckian two-country stock-flow consistent (SFC) simulation model, we shed light on different regimes in modern finance-dominated capitalism, their interaction at the global scale, and then on the changes in regimes after the 2007-09 crises. Most importantly, we present the main features of a progressive and more stable equality-, sustainability- and domestic demand-led regime. We show that the main features of such a regime will have to focus on a 'reformed capitalism' with regulated finance, a more equal distribution of income and active government fiscal policies, as guide posts for progressive social democracy.
Keywords: B59; E02; E11; E12; E25; E65; F41; O41; 330; debt; financialisation; growth regimes; inequality; post-Keynesian macroeconomics; social capitalism; stock-flow consistent model